f(x) = – x sinx
f ’(x) = 2x – sin x – x cos x
⇒ 0 sin x 1, 0 cos x 1,
⇒ 2x–sin x –x cos x > 0
⇒ f ’(x) ≥ 0
Hence,f(x) is an increasing function on ().
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
Show that the altMathematics - Board Papers